Skateboarding and contested public space in Portrush, Northern Ireland: exploring tensions between resortification and DIY space-claiming through co-creative methodology - Donaghey, J.; Browne, J. (Sport in Society: Cultures, Commerce, Media, Politics, 2025)
The seaside town of Portrush, on the north coast of Ireland, has a strong reputation for skateboarding culture. The Skate Stopped? co-creative research project is a critical intervention in the campaign to `Get Portrush a Skatepark!`, collaborating with the community to raise the profile of skateboarding`s cultural tradition in the area, and engaging the skaters in critical dialogue in this gentrifying context. This article focuses on the project`s video outputs (as published between April and October 2023), picking out two key critical themes: Do-It-Yourself (DIY) culture and space-claiming; and resortification (gentrification in a touristic context). We argue that any contemporary campaign that engages in DIY space-claiming constitutes (at least partially) a critique of neoliberalism—the limitations of skateboarding in Portrush in this regard and the vulnerability to co-optation within a resortifying dynamic are discussed, while exemplifying the insights that can be garnered through co-creative videographic research methodologies.